Long-range order in linear ferromagnetic oscillator systems. Strong pair quadratic n-n potential - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
Long-range order is proved to exist for lattice linear oscillator systems with ferromagnetic potential energy containing a term with strong nearest-neighbor (n-n) quadratic pair potential. A contour bound and a generalized Peierls argument are used in the proof.